Evolution of the Keivy domain in the Precambrian - Kozlov N. E.; Sorokhtin N. O.; Marchuk T. S. (Vestnik MGTU, 2023)
Detailed geological and petrogeochemical studies carried out using the techniques developed by the authors have made it possible to complete the picture of the formation of supracrustal complexes of the Keivy structure. The studies have shown that the metasedimentary complexes of the Chervurt and Vykhchurt suites were formed mainly due to the material of the underlying strata. In the development of the Vykhchurt Formation, starting from its upper part, the material of the domains surrounding the Keivy takes an active part. The authors have come to the conclusion that at least the middle part of the Keivy section was formed as a result of washing and redeposition of the material of the structure itself, it confirms the conclusions about the presence of redeposited weathering crusts within the Keivy. The results obtained testify to the correctness of the earlier conclusion about the formation of the Keivy structure under conditions most similar to the middle massifs, and to a certain extent explain the formation of a giant deposit of aluminum raw materials within the Keivy.